MOA Framework and Website Quality as Creator of Attitude and Behavioral Consequences - Whony Rofianto (Jurnal Ilmu Manajemen & Ekonomika, 2016)
This study aimed to examine the factors driving the establishment of user satisfaction on the campus website. The study focused on two exogenous constructs, namely website quality as the external aspects and the MOA framework (especially motivation and ability) as the internal aspects for users of the campus website. The study also tried to examine the dual implications of user satisfaction, toward the intention to revisit on one side, also toward attitude and word-of-mouth intention on the campuses itself on the other side. This study was conducted using descriptive research design approach. A total of 210 cross-sectional data collected through an offline and online survey on student sample of state and private universities in the JABODETABEK area. Data analysis and hypothesis testing was executed using Structural Equation Model. The analysis of empirical data indicates a positive impact of website quality on user satisfaction. Furthermore, user satisfaction proven to give positive implications toward revisit intention on the one hand, and the attitude toward the brand on the other side, which in turn encourages word-of-mouth intention. Meanwhile, opposite findings on the effect of the MOA framework on user satisfaction, it gives a new insight that amplify the urgency of the implementation of campus website by higher education providers.